2000
DOI: 10.1002/1097-4652(200011)185:2<293::aid-jcp14>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Induction ofMRP1 and ?-glutamylcysteine synthetase gene expression by interleukin 1? is mediated by nitric oxide-related signalings in human colorectal cancer cells

Abstract: Treatment of human colorectal cancer cells HT29 with interleukin 1beta (IL-1beta) induces expression of the multidrug resistance protein (MRP1) gene encoding the ATP-dependent glutathione S-conjugate export (GS-X) pump and the gamma-glutamylcysteine synthetase (gamma-GCSh) gene encoding heavy (catalytic) subunit of gamma-glutamylcysteine synthetase, the rate-limiting enzyme for the biosynthesis of glutathione (GSH). The induction can be suppressed by N(G)-methyl-L-arginine, a specific inhibitor of nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…We demonstrated previously that expression of ␥-GCSh could be induced by many cytotoxic agents, including antitumor agents (10,11), heavy metals (11), carcinogens (12), and prooxidants (13)(14)(15)(16). All of these treatments, to various extents, induce intracellular reactive oxygen species imbalance.…”
mentioning
confidence: 79%
“…We demonstrated previously that expression of ␥-GCSh could be induced by many cytotoxic agents, including antitumor agents (10,11), heavy metals (11), carcinogens (12), and prooxidants (13)(14)(15)(16). All of these treatments, to various extents, induce intracellular reactive oxygen species imbalance.…”
mentioning
confidence: 79%
“…Changes at the post-transcriptional level such as protein stability could also be involved. An induction of Mrp1 mRNA expression was seen also in IL-1␤-treated Hepa 1-6 cells, similar to that which has also been reported in human hepatoma cells (Ikegami et al, 2000;Lee and PiquetteMiller, 2001). Likewise, neither Mrp-mediated efflux of 5-CF nor mRNA levels were significantly altered by treatment with bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…As with ␥-GCSh, our laboratory has demonstrated that expression of MRP1 in cultured cells can be induced by a variety of cytotoxic agents, including prooxidants (155), heavy metals (109), carcinogens (282), antitumor agents, and nitric oxides (106). These observations raise an interesting scenario that mechanisms underlying induced expression of MRP1 and ␥-GCSh may be co-regulated.…”
Section: Mrp Familymentioning
confidence: 96%
“…Transcriptional regulation. Our laboratory previously demonstrated that expression of ␥-GCSh can be induced by a number of cytotoxic challenges, including antitumor agents (77,109), heavy metals (109), carcinogens (282), and prooxidants (106,282). All these inducers, at the concentrations used, exert various degrees of oxidative stresses.…”
Section: Redox Regulation Of Multidrug Resistance 109mentioning
confidence: 99%